A Meta-Analysis of the Relationship between Attitude toward Mathematics and Mathematics Anxiety: The Sample of Turkey - Hakan Bayırlı; Mehmet Ertürk Geçici (Sakarya University Journal of Education)
This study aims to obtain a more comprehensive result for the studies examining the relationship between attitude toward mathematics and mathematics anxiety in Turkey. To this end, this study employed the meta-analysis method, and the results of the independent studies were combined statistically. A meta-analysis was conducted with 19 studies according to the inclusion criteria, and 21 effect-size values were calculated for these 19 different studies. The study revealed that the total sample size of the studies included in the meta-analysis was 8874. In the study, the mean effect size of the relationship between attitude toward mathematics and mathematics anxiety was -.566. This value obtained according to Fisher z corresponded to approximately -.512 when converted to the Pearson r value. This effect size indicated a high-level negative relationship between attitude toward mathematics and mathematics anxiety. The moderator analysis demonstrated that while the effect sizes did not differ in terms of school level, publication type, publication year, and sample size variables, they differed in terms of the research region variable.